Quantitative Raman Spectroscopic Determination of the Composition, Pressure, and Density of CO2-CH4 Gas Mixtures - Chen, Ying; Chou, I-Ming (Journal of Spectroscopy, 2022)
The Raman spectra for pure CO2 and CH4 gases and their ten gas mixtures were collected at pressures and temperatures ranging from 2 MPa to 40 MPa and room temperature (∼24°C) to 300°C, respectively. A systematic analysis was carried out to establish a methodology for the quantitative determination of the composition, pressure, and density of CO2-CH4 mixtures. The shift in the peak position of the υ1 band for CH4 was sufficiently large to enable the accurate determination of the pressure of pure CH4 and CH4-dominated fluids (>50 mol% CH4). An equation representing the observed relationship of the peak position of the υ1 band of CH4, density, and composition was developed to calculate the density of CO2-CH4 mixtures. The Raman quantification factor F (CH4)/F (CO2) was demonstrated to be near a constant value of 5.048 ± 0.4 and was used to determine the CH4 to CO2 molar ratio in an unknown CO2-CH4‐bearing fluid with high internal pressure (>10 MPa) based on the Raman peak area ratio. The effect of temperature on the variation in Raman spectral parameters was also investigated at temperatures up to 300°C. The results showed that the effect of temperature must be considered when Raman spectral parameters are used to calculate the pressure, density, and composition of CO2-CH4 gas mixtures. Raman spectroscopic analysis results obtained for six samples prepared in fused silica capillary capsules were validated by comparison with the results obtained from microthermometry measurements.